Bureaucratic Behavior, Service Infrastructure, and Community Satisfaction in Public Services: Evidence from Population Administration Services in Ambon City, Indonesia - Suripatty, Chiquitita Anastasya Bernadine; Ponto, Iriane Sosiawaty; Patty, Julia Theresia (Journal of Social Knowledge Education (JSKE), 2026)
Purpose of the study: This study aims to determine the influence of bureaucratic behavior and facilities-infrastructure on community satisfaction in population administration services at the Department of Population and Civil Registration of Ambon City. Methodology: This study employed a quantitative survey approach involving community members who had directly accessed population administration services at the Department of Population and Civil Registration of Ambon City as the research subjects. Data were collected using structured Likert-scale questionnaires designed to measure bureaucratic behavior, service facilities–infrastructure, and community satisfaction, with instrument validity and reliability tested prior to analysis. The collected data were analyzed using SPSS software through descriptive statistics and multiple linear regression analysis to examine the relationships and influence among variables, supported by classical assumption tests (normality, multicollinearity, heteroskedasticity, and autocorrelation) to ensure the reliability and robustness of the regression model. Main Findings: The study concludes that bureaucratic behavior and service facilities–infrastructure play a crucial role in shaping community satisfaction with population administration services. These findings imply that public policy should prioritize not only infrastructural improvements but also bureaucratic professionalism, transparency, and responsiveness to strengthen public trust. The study contributes to public administration scholarship by emphasizing social satisfaction as a key indicator of effective and citizen-oriented public service delivery. Novelty/Originality of this study: This study offers a new integrated analysis that simultaneously examines bureaucratic behavior and facilities-infrastructure in the context of population administration services in Ambon City. It contributes to existing knowledge by presenting localized empirical evidence and highlighting the combined influence of human and structural service components on public satisfaction.